Adipositas Management Versorgung, Betreuung und Behandlung in Anästhesie, Chirurgie, Intensivmedizin und Notfallmedizin - Lewandowski, Klaus; Bein, Thomas (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2012)
Overweight and obesity are increasing worldwide: In Germany, the majority of adults are overweight or obese, and it is almost a quarter among children and adolescents. Obesity means serious health risks and problems for those affected, which can become life-threatening in the context of emergency or hospital treatment. The large number of concomitant diseases and the pathophysiological changes in the respiratory system and the cardiovascular system lead to a significantly increased risk of perioperative complications. To control these risks, special processes and treatment management are necessary: ​​integrated concepts for preoperative evaluation, for adequate airway management with an adapted anesthetic control, as well as for intensive therapy and pain therapy. In addition, these patients require specially trained hospital and rescue personnel, suitable equipment and adequate structural equipment, which all hospitals and healthcare facilities will have to take care of in the future. This practice manual comprehensively conveys the theory and practice of the special requirements, concepts and structures for the treatment and care of overweight or obese adults and children.